Analisis Efektivitas Sistem Pemindahan Sampah “Surung Sintak” di Kota Banjarmasin - Bella Nadya Safitri; Muhammad Firmansyah; Andy Mizwar; Muhammad Abrar Firdausy (Jernih: Jurnal Tugas Akhir Mahasiswa, 2026)
The narrow area and dense population in Banjarmasin have made it difficult to find land to build TPS in each village so that one TPS can serve several villages. The uneven distribution of TPS in each urban villages resulted in several residential areas being relatively far away to reach the available TPS. These problems made the Banjarmasin City Environment Service create a new innovation, namely "Surung Sintak". "Surung Sintak" is a South Kalimantan tradition, which means handed over and taken. The application of "Surung Sintak" to the waste removal innovation created by the DLH of Banjarmasin City is that waste is handed over by collection officers, which will then be or be received by "Surung Sintak" officers to be put into garbage trucks. The determination of the Surung Sintak service area was carried out by the village administration proposing it to DLH Banjarmasin. Waste collection is carried out by collection officers. Waste transfer is carried out at a mutually agreed time and location with an estimated time of 2 hours at one service point. Waste transportation is carried out by one driver and three people who help, using a transporter, namely a compactor truck. Judging from the distance, the transfer of "Surung Sintak" is more effective than disposing of waste to conventional TPS. Surung Sintak's operational costs are Rp. 87,300,000 less than conventional TPS because the wages for workers, maintenance, and equipment for Surung Sintak are lower than conventional TPS. Keywords: Waste Transfer, Surung Sintak, Effectiveness.